La ciencia en el desarrollo de América Latina - Herrera, Amilcar O. (Estudios Internacionales, 1968)
The relative backwardness of Latin America with respect to developed countries is known in everything that refers to scientific and technological research. Most of the scientific research being done bears little relation to the most pressing needs of the region. Basic research carried out in the region takes place mainly at universities or institutes related to them or with state agencies. With rare exceptions, this research plans bear no relation to the needs of the industry or to the general problems of economic development in the region. What are the causes of scientific and technological backwardness in Latin America? It is obvious that the correct answer to this question is of fundamental importance, since it is the indispensable prerequisite for the planning of any policy that tends to overcome this delay.